Risk Factors of Maternal Death in Karanganyar, Central Java, Indonesia - Kusnadi, Noferi; Respati, Supriyadi Hari; Sulistyowati, Sri (Journal of Maternal and Child Health, 2019)
Background: The maternal mortality rate is an indicator of national health status. To reduce the Maternal Mortality Rate (MMR), especially in Karanganyar Regency, the risk factors that affect maternal mortality must be known. Subjects and Method: